Experimental and Theoretical Investigation of Overburden Failure Law of Fully Mechanized Work Face in Steep Coal Seam - Ze Liao; Tao Feng; Weijian Yu; Genshui Wu; Ke Li (Advances in Civil Engineering)
In this study, both theoretical analysis and similar simulation experiment are employed to investigate the overburden failure law of fully mechanized face in the steep coal seam. By establishing the mechanical model of inclined rock beam, the deflection equation of overlying strata beam is obtained. Based on the geological conditions of Xiangyong coal mine in Hunan Province of China, the laws of roof deformation and failure in steep coal seam are obtained by similar simulation experiments. The results showed that the roof deformation of the goaf is relatively large after the working face advances along the strike, and the deformation mainly occurs in the upper roof of the goaf. The backward gangue in the immediate roof fills the lower part of the goaf, which plays a supporting role in the lower part of the roof and floor. The roof fracture of goaf is located in the middle and upper parts of the working face, which is consistent with the results derived from the mechanical model. After the roof fracture, a “trapezoid” bending fracture area and the secondary stability system area is formed, which is composed of four areas: the lower falling and filling support area, the upper strata bending fracture area, the fracture extension area, and the roof bending sinking area.